A guidance on diagnosis and management of hyperglycemia at COVID care facilities in India. Issue 1 (January 2021) - Gupta, Yashdeep; Goyal, Alpesh; Kubihal, Suraj; Golla, Kiran Kumar; Tandon, Nikhil
Abstract: Background and aims: Diabetes and coronavirus disease 2019 (COVID-19) share a bidirectional relationship. Hyperglycemia occurring in the setting of either previously diagnosed or undiagnosed diabetes is known to be associated with poor outcomes. Here, we aim to provide a simple and practical guidance on the diagnosis and management of hyperglycemia in admitted patients with COVID-19. Methods: The guidance is formulated based on experience of authors and relevant literature on the subject searched using Pubmed. Results: Every patient admitted to a COVID care facility should be investigated for hyperglycemia using a combination of tests including capillary blood glucose, fasting plasma glucose and HbA1c. Oral glucose lowering drugs can be considered in patients with mild COVID illness who have mild hyperglycemia [pre-meal blood glucose of <180 mg/dl (10 mmol/L) and post-meal blood glucose of <250 mg/dl (13.9 mmol/L)] and no contraindication to the use of these agents.. All patients with moderate-severe disease and/or hyperglycemia of greater severity should be initiated on insulin therapy. Hyperglycemia should be aggressively screened for and managed in patients receiving systemic glucocorticoids. Conclusion: This document provides a broad overview on the diagnosis and management of hyperglycemia at COVID care facilities and should be useful to a wide range of healthcare personnel involved in care of patients with COVID-19. Highlights: Hyperglycemia is associated with poor outcomes among patients with COVID-19. Strategies for screening of hyperglycemia in patients with COVID-19 have been highlighted. Strategies for management of inpatient hyperglycemia, including steroid-induced hyperglycemia have been highlighted.